(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Polypharmacy, the concurrent use of multiple medications, poses significant challenges for elderly patients due to the increased risk of adverse drug reactions and medication-related complications. Nurses play a pivotal role in mitigating these risks through effective medication management practices. Drawing on pharmaceutical perspectives, this article provides insights for nurses to navigate the complexities of polypharmacy in elderly patients. Key strategies include comprehensive medication reviews, rational prescribing practices, individualized treatment plans, patient education, and monitoring. By integrating pharmaceutical expertise with nursing care, healthcare providers can optimize medication use, enhance patient safety, and improve outcomes for elderly individuals.